Analysis of Monostatic SAR Processing Techniques to Focus Stationary Bistatic Airborne Data - Rodriguez-Cassola, Marc; Krieger, Gerhard; Wendler, Michael (International Radar Symposium, IRS 2005, 2005)
Bistatic SAR data focussing stands out as a fundamental issue to facilitate further research and applications in remote sensing. Among the many bistatic configurations which can be thought of, the stationary surveys keep a capital feature of the monostatic SAR systems, the azimuth-invariance. This paper adresses the processing of stationary bistatic airborne SAR data in the presence of motion errors. The time-domain solution stands as the easiest way to focus the data including full motion compensation. A derivation of the point response in range-Doppler domain is presented. Using this result, efficient bistatic focussing solutions based on range-Doppler (RD) and extended chirp scaling (ECS) algorithms are analysed. Particular implementation problems, like Doppler parameter estimation errors and motion compensation are also addressed. The included algorithms are tested with real data from the DLR-ONERA bistatic airborne campaign.
DLR Import::2019-04-03